2012
DOI: 10.1134/s1070427212020085
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption properties of surface of carbon materials at extremely low coverages

Abstract: Adsorption properties of blacks and their graphitized analogues were examined by the inverse gas chromatography at extremely low surface coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…We examined in Section the adsorption properties of N 2 on two nonoxide materials: carbon black and graphitized carbon. It is well reported in the literature that both of these materials vary in heterogeneities due to the differences in their functional groups, graphitic domains, and imperfections. , Nitrogen adsorption studies have been reported extensively on these two carbons ,, to reveal their surface properties. The surface characterization of such carbon materials is usually done by the BET method using the adsorption data in a narrow low-pressure range, which is generally marked by micropore filling ,, and/or phase change of the adsorbate on graphitic basal planes. , The current ZAI analysis avoids these heterogeneities to determine the thermodynamic isotherms.…”
Section: Discussionmentioning
confidence: 99%
“…We examined in Section the adsorption properties of N 2 on two nonoxide materials: carbon black and graphitized carbon. It is well reported in the literature that both of these materials vary in heterogeneities due to the differences in their functional groups, graphitic domains, and imperfections. , Nitrogen adsorption studies have been reported extensively on these two carbons ,, to reveal their surface properties. The surface characterization of such carbon materials is usually done by the BET method using the adsorption data in a narrow low-pressure range, which is generally marked by micropore filling ,, and/or phase change of the adsorbate on graphitic basal planes. , The current ZAI analysis avoids these heterogeneities to determine the thermodynamic isotherms.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous communication [15] we reported the basic surface characteristics of the carbon blacks considered in the present study and described in detail procedures used to prepare the given adsorbents for a chromatographic analysis.…”
Section: Methodsmentioning
confidence: 99%
“…where γ CH 2 (mJ m -2 ) is a part of the free energy, which corresponds to adsorption of a single CH 2 group, γ CH 2 = 35.6 + 0.058[293 -T(K)] [19]; σ CH 2 , surface area of a methylene unit in n-alkanes (0.06 nm 2 ); Δ(G -°1 ,C ) CH 2 , adsorption energy of a CH 2 group on the given adsorbent, which can be calculated as (2) Values of V A,1 were determined from experimental retentions of n-pentane and n-hexane by the method described in detail in [15,16]. The working temperature range was 373-473 K. It should be noted that the values of V A,1 were found under conditions close to zero surface fi lling [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation